Herbage mass and chemical composition of the heterogeneous grasslands affected by harvesting time in Subtropical terrain Nepal - Pandey, Prabin; Bhusal, Tej Narayan; Pandey, Thaneshwar; Sharma, Surya Prasad; Barsila, Badrika Devkota; Barsila, Shanker Raj (Journal of Agriculture and Natural Resources, 2019)
A study was carried out to evaluate the productivity and chemical composition of heterogeneous grasslands at Agriculture and Forestry University (AFU) livestock farm. The four grassland ecotypes were chosen as upland north, upland south, lowland south and lowland north. The dominating herbage species and cover abundance by the botanical groups were studied on day before the harvesting. Later, the herbage dry matter productivity was estimated by quadrat cutting during May and June, 2017. Chemical analysis was done by using the proximate method for dry matter (DM), crude protein (CP), crude fiber (CF) and ether extract (EE) content. Research results showed that the AFU grassland dominated by perennial grasses and sedges followed by the forbs. The mean coverage of grasses and sedges was about 55%, whilst that of forbs was about 29% and the least was for legumes (about 4%). The cumulative herbage mass was about 1.53 t/ ha on the DM basis, whilst the highest DM was found in the upland-south (1.74 t/ha) and the least was in the upland-north (1.334 t/ha). The proximate analysis further revealed that the site had no effect on CF content, whilst the CP was significant only at the second harvest for the lowland north (8.34%). Data revealed that the herbage composition might depend upon the soil moisture availability and geographical aspect. The dominance of perennial grasses at AFU grasslands revealed the yield stability, but needs the improvement through inoculation with leguminous forages for improved feed quality.